Study of physicochemical characterization of potassium-doped Nafion117 membrane and performance evaluation of air-breathing fuel cell in different alkali-methanol solutions. (15th October 2016) - Alipour Najmi, Ali; Rowshanzamir, Soosan; Parnian, Mohammad Javad
Abstract: Direct methanol alkaline fuel cell (DMAFC) using a cation exchange membrane (CEM) was operated in passive condition and compared to passive direct methanol fuel cell (DMFC). A polymer electrolyte membrane for passive DMAFC was prepared by immersing Nafion117 membrane into KOH solution at temperature of 80 °C. The prepared membrane (potassium-doped Nafion117) exhibited higher mechanical properties and thermal stability than Nafion117. Ionic conductivity of K + form Nafion117 membrane was measured to be lower than that for pristine Nafion117. Single cell in alkaline condition (passive DMAFC) exhibited better cell performance than that in the cell using Nafion117 in acidic condition (passive DMFC). The open circuit voltage (OCV) of passive DMAFC reached to about 1 V which was considerably higher than that for passive DMFC (0.45 V). The methanol crossover rate through membranes was also measured and the results implied that the potassium-doped Nafion117 membrane had lower permeability to methanol. Highlights: Application of K + form of Nafion117 membrane in passive DMAFC. Investigation of KOH and methanol concentrations effects on the performance of passive DMAFC. Higher peak power density and OCV for passive DMAFC than passive DMFC.